(untitled) (Bulletin of the International Association for Paleodontology, 2025)
This case study focuses on two rare dental anomalies – unilateral microdontia and bilateral hypodontia – identified in two female skeletons excavated in a shared burial from the medieval and early modern cemetery of St. Euphemia in Rovinj, Croatia. Detailed anthropological and radiological analyses revealed the presence of microdontia in the right maxillary third molar of individual SU 298 and hypodontia affecting the maxillary lateral incisors of individual SU 299. These findings contribute to the understanding of dental variation in archaeological contexts and highlight the influence of genetic and environmental factors on these anomalies. The co-occurrence of anomalies and the shared burial context suggest a potential familial link, underlining the importance of integrating bioarcheological with molecular studies. This article provides deeper insight into the health of individuals and the wider population in Rovinj between the 15th and 17th centuries.